MINAT MAHASISWA UNTUK BERWISATA KE NEGERA INDIA (Studi Kuantitatif dengan Treatment konten YouTube berjudul Rape is consensual: Inside Haryana’s Rape Culture) - Nurhayani Saragih; Enjang Pera Irawan (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2018)
Almost all countries are trying to launch tourism as a source of foreign exchange earners for their countries. Many efforts have been made to increase the number of tourists visiting. One of the tourist destinations that once entered the 7 (seven) wonders of the world is Taj-Mahal. The palace was made for 22 years by Mughal Emperor Shah Jahan for his empress. With such conditions, India is one of the tourist destinations that are worth visiting. In addition to the king's palace, India has a different culture from Indonesia. Meanwhile, along with the development of communication technology, the number of YouTube content containing documentation about culture is increasing. YouTube viewers are also increasing in number dayly. One YouTube video of documentation of Indian culture, is entitled Rape is consensual: Inside Haryana’s Rape Culture, which will be an instrument as a treatment to see if there is a difference in interest in visiting India before and after watching the YouTube video. This study uses quantitative research methods by distributing questionnaires to 58 Mercu Buana University students who were selected purposively. That study aims to find out whether there are differences in interests between before and after watching YouTube content. The results showed that even though there was a decrease in the mean value from 12.121 (before treatment) to 10.345 (after treatment), the calculation of the t value calculated was 5.092 while the t-table value for the two-tailed test (Two Tail) was 2.002. The t value calculated is greater than the t-table value, so it can be concluded that there is no difference in traveling interest to India before and after watching the YouTube video.